2016
DOI: 10.1021/acs.joc.5b02873
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Halogenation and Cyanation of Electron-Deficient Aryl Carboxylic Acids via Cu Mediator as Well as Electron-Rich Ones through Pd Catalyst under Aerobic Conditions

Abstract: Simple strategies for decarboxylative functionalizations of electron-deficient benzoic acids via using Cu(I) as promoter and electron-rich ones by employing Pd(II) as catalyst under aerobic conditions have been established, which lead to smooth synthesis of aryl halides (-I, Br, and Cl) through the decarboxylative functionalization of benzoic acids with readily available halogen sources CuX (X = I, Br, Cl), and easy preparation of benzonitriles from decarboxylative cyanation of aryl carboxylic acids with nonto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 102 publications
1
31
0
1
Order By: Relevance
“…[CAS: 609-73-4]. 26 Yellow solid, 108.6 mg, 87% (isolated yield), mp 48–49 °C; 1 H NMR (400 MHz, CDCl 3 ): δ 8.05 (d, J = 8.3 Hz, 1H), 7.87 (d, J = 8.3 Hz, 1H), 7.50 (t, J = 7.7 Hz, 1H), 7.25–7.29 (m, 1H); 13 C{ 1 H} NMR (100 MHz, CDCl 3 ): δ 153.1, 142.0, 133.5, 129.2, 125.6, 86.3; MS (EI) [M] + m / z = 249.…”
Section: Methodsmentioning
confidence: 99%
“…[CAS: 609-73-4]. 26 Yellow solid, 108.6 mg, 87% (isolated yield), mp 48–49 °C; 1 H NMR (400 MHz, CDCl 3 ): δ 8.05 (d, J = 8.3 Hz, 1H), 7.87 (d, J = 8.3 Hz, 1H), 7.50 (t, J = 7.7 Hz, 1H), 7.25–7.29 (m, 1H); 13 C{ 1 H} NMR (100 MHz, CDCl 3 ): δ 153.1, 142.0, 133.5, 129.2, 125.6, 86.3; MS (EI) [M] + m / z = 249.…”
Section: Methodsmentioning
confidence: 99%
“…The challenges of developing a general metal-catalyzed iododecarboxylation reaction of aromatic carboxylic acids have been summarized in a very recent paper by the Cai research group who also report a copper-mediated method for this transformation. 75 They found that electron-deficient aromatic carboxylic acids bearing ortho-nitro groups could undergo efficient iododecarboxylation under aerobic conditions in the presence of stoichiometric amounts of copper(I) iodide, while electron-rich variants required the addition of catalytic palladium acetate to facilitate the transformation (Scheme 29). Heteroaromatic carboxylic acids, including benzofurans, benzothiofurans, and indoles, also gave iodinated products under these conditions.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…8 There are several reported methods for performing decarboxylative halogenation on aromatic substrates, but they often rely on metal catalysts, require high reaction temperatures, or are unselective. [9][10][11] Recent reports by Larrosa and co-workers have advanced this area of research, but their method requires stoichiometric quantities of a base and relatively high reaction temperatures. 12,13 We recently reported a metal-free selective decarboxylative halogenation of heteroaromatic compounds under mild conditions (Scheme 1).…”
mentioning
confidence: 99%